Methods of Control of the Leishmania infantum Dog Reservoir: State of the Art - Michele Podaliri Vulpiani; Luigi Iannetti; Daniela Paganico; Filomena Iannino; Nicola Ferri (Veterinary Medicine International)
Leishmania infantum is a protozoan parasite causing severe vector-borne visceral diseases both in humans and dogs. The latter are the most important natural reservoir and therefore should be the main target of control measures. The real efficacy of seropositive dogs culling as a direct control method is still debated, and the new sensitivity of large part of population considers ethically unacceptable this kind of approach. Treatment of infectious dogs with one of the available therapeutic protocols is recommendable as it allows to reduce parasite burdens and therefore the possibility of transmission of Leishmania infantum to vectors. Vaccination has been proven to be a very effective control tool, but the absence of a commonly recognized diagnostic method able to distinguish vaccinate from seropositive individuals is still an important limit. Concerning indirect control methods, a number of studies have demonstrated the efficacy of topical insecticides treatment (collars, spot-on, and sprays) in reducing incidence and prevalence of L. infantum. Also, the reduction of the odds of seroconversion in humans in endemic areas has been reported after the application of indirect control measures on dogs. The contemporary use of direct and indirect methods is even more effective in reducing seroprevalence in dogs.